Tactile Sensors for Robotic Applications - Pirozzi, Salvatore (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The book covers different aspects: - Innovative technologies for tactile sensors development - Tactile data interpretation for control purposes - Alternative sensing technologies - Multi-sensor systems for grasping and manipulation - Sensing solutions for impaired people